How did a successful New Zealand wine company develop relationships in China to support its market entry? - Lin, Fujing (Auckland University of Technology, 2014)
China has taken the position of second largest economy in the world during the period the Chinese government applied economic reforms and an open-door to incoming foreign direct investment policy from December 1978. The rapidly growing economy has provided huge opportunities for the world. Recently the amount of New Zealand (NZ) exports to China has increased from NZ $2.3 billion (2008) to NZ $ 6.7 billion (2012). However, the export of wine to China, the subject of this research project, only represents a small proportion of these total exports (New Zealand Trade and Enterprise n.d. a). For this study, a NZ wine company was selected from the finalists in the HSBC (the Hong Kong and Shanghai Banking Corporation) New Zealand China Trade Association (NZCTA) China Business Awards for 2013. The purpose was to identify a successful wine company’s best practices for conducting business in China and share them with other companies. In this study, interview questions were designed to respondents on strategies for international business operations, assessing the business environments, the barriers and challenges in China market, and the factors to the business success from literature review. The semi-structured interviews were conducted face-to-face with the Managing Director and Marketing Manager in the company headquarters office, and with the Brand Manager in China, via internet chatting at different times, based on thirty questions that represented the research relevant issues. Four themes emerged from the findings. Firstly, the company entered the Chinese market driven by the opportunity perceived as stemming from the very large population, the rapid increase in high income groups, and the changing perceptions of drinking grape wine. Secondly, the company has gone through four stages of market entry which represented the process of their business relationship development. They have not only endured a failure of distribution but also have entered into an exciting phase. Their persistence could be one of the reasons for their success. Thirdly, the company has established very strong guanxi relationships in the Chinese market including multiple distributors and different channels for sales after eight years of doing business in China. Finally, this researchhas identified the important factors in achieving business success from many aspects; employing a local manager in China was the biggest factor in the company achieving its goals. In addition, the company’s long term vision, competitive advantages, flexibility and full use of resources all played significant functions in the business success. From this research, the findings have reflected the similarities with previous research about doing business in China, such as language, cultural difference, complicated relationship , gift-giving, banquets, reciprocal of favour, ‘face’ and ‘renqing’. However, many channels for product sales in China are different from Western countries. For example; one channel is that of government which takes many banquets which can be unstable or risky, if the Central Government of China prohibits banquets, then the sale channel will be closed. Therefore, too much emphasis should not be placed on this channel. The target should be the groups with high incomes in China’s urban areas.
Keywords: Market entry strategies; Relationship building